Slight Intellectual Disability Students’ Creative Originality of Expression Changes in Technology Lessons - Petrulionienė, Vida; Valantinaitė, Ilona (Pedagogika, 2015)
This article analyzes the slight intellectual disability students ‘creative originality expression in technology lessons. Technological development consists of four areas: textiles, nutrition, construction materials and electronics. The authors organize and implement educational experiment: with the help of information technology in the educational process by technological development areas using visual creativity stimulation techniques. At the beginning and end of the educational experiment conduced diagnostic test sections. Comparing the data obtained by the above-mentioned sections change, showing the visual methods in the educational process of slight intellectual disability students‘ creative expression of originality technology lessons. Informants creative originality is measured by the article’s authors selected seven creative originality of expression evaluation criteria. The research problem: what is a slight intellectual disability students‘ creative originality of expression change in technology lessons using visual methods of education, and technology education in the areas where it occurs the most. The research problem: what is a slight intellectual disability students‘ creative originality expression change in technology lessons using visual methods of education, and technology education in the areas where it occurs the most. Object – slight intellectual disability students‘ creative originality. Purpose – to assess slight intellectual disability students‘creative originality of expression changes in technology lessons using visual education methods. Investigation methods: analysis of scientific literature and documents; qualitative study – educational experiment. The first section of the diagnostic data revealed that a slight intellectual disability students characterized by realistic, distinctive creative originality, which is mostly revealed in objects decoration. It should be noted that there is a necessary condition - the principles of humanism based on the learner and educator relationship. Second section of the diagnostic analysis of the data showed that a stimulation of slight intellectual disability students more creativity from the reality of distant subjects, the originality of creative expression become more liberal, and expression of the mean values generally increase. Noticeable signs of change in objects decoration - from the everyday, real parts toward imaginary, unseen objects. An important fact that a slight intellectual disability students‘ created objects unrealistic plot is positive, demonstrating altruism, assistance to the other, efforts for the general welfare, felt empathy. In safe environment for creative expression slight intellectual disability students are enjoying the creative process, expressing his admiration for the work of others, and are encouraged to act themselves and others. Construction materials area can be identified as the most favorable area for slight intellectual disability students to the creative expression of originality. The field from the task I and II diagnostic sections found during the highest creative expression results. A little lower estimates of nutrition in the field of creative tasks. It should be noted that the subjects of the creative originality of expression gain estimates show that a slight intellectual disability students‘ creative stimulation more distant from the reality of visual objects encourages students creative expression of originality in all areas of technology education.